Estimation of Some Heavy Elements in Different Marine Samples Collected from the Beaches of Zawiya City - Mabrouka M. Hamzah; Salem A. Jebirl; Abtisam S. Aljarmi; Najah Y. Baroud; Rania A. Alrwesse (African Journal of Advanced Pure and Applied Sciences, 2025)
This study assessed heavy metal (cadmium, lead, and arsenic) contamination in fish, algae, and seawater samples from the coast of Zawiya, Libya. Concentrations were determined using Atomic Absorption Spectrophotometry (AAS) after appropriate sample digestion. Results showed that all metal concentrations in fish and seawater were below detection limits, indicating they are currently safe for human consumption and the environment. In contrast, certain marine organisms demonstrated a significant capacity for bioaccumulation of these metals. A sample of seaweed (Posidonia oceanica) showed a cadmium concentration of 9.6 mg/kg, which exceeded the internationally permissible limit of 5.5 mg/kg. Similarly, brown algae accumulated a high concentration of arsenic (26.6 mg/kg), highlighting its role as a biomonitor. These findings underscore the importance of using algae and seagrasses as effective bioindicators for monitoring heavy metal pollution in coastal ecosystems, even when contamination is not evident in fish or water.